Dynamics and Functional Interplay of Nonhistone Lysine Crotonylome and Ubiquitylome in Vascular Smooth Muscle Cell Phenotypic Remodeling - Cao, Shan-Hu; Chen, Zhi-Huan; Ma, Ru-Yuan; Yue, Lin; Jiang, Han-Mei; Dong, Li-Hua (Frontiers in Cardiovascular Medicine, 2022)
Background: Crotonylation of histones is a recently discovered type of post-translational modification that can regulate gene expression. However, the function of crotonylation on nonhistone proteins in vascular smooth muscle cells (VSMC) is unclear. Here, we aim to use modification and proteomic analysis to find the cellular characteristic of crotonylated nonhistone proteins and the crosstalk with ubiquitinated proteins in vascular smooth muscle cell (VSMC) phenotypic remodeling. Methods: We performed modification and proteomic analysis of VSMCs before and after platelet-derived growth factor-BB (PDGF-BB) stimulation. The crotonylated and ubiquitinated pan-antibody was used to enrich the protein and then subjected to high-throughput mass spectrometry analysis. Then we compared the enrichment analysis of differentially modified proteins in regards to GO terms, KEGG pathway and protein domain. Results: As a result, there were 2138 crotonylation sites in 534 proteins and 1359 ubiquitination sites corresponding to 657 proteins. The crotonylated proteins participate in a variety of important cellular pathways and perform different functions in VSMCs. Among them, some proteins were found to be closely involved in the physiological process of VSMC phenotypic remodeling including glycolysis/gluconeogenesis, vascular smooth muscle contraction, and PI3K-Akt signaling pathway. Furthermore, the KEGG pathway enrichment analysis showed that the ubiquitinated proteins were found to be closely involved in the physiological process of VSMC phenotypic remodeling including glycolysis/gluconeogenesis, vascular smooth muscle contraction, RAS signaling pathway or PI3K-Akt signaling pathway. Crosstalk analysis showed that there were 199 sites within 177 proteins modified by crotonylation and ubiquitination simultaneously. PPI network analysis indicated that crotonylated and ubiquitinated proteins played an important role in cellular bioprocess commonly and possible synergistic effect. Conclusions: In summary, our bioinformatics show that nonhistone crotonylation and ubiquitination play an important role in the VSMC phenotypic transformation induced by PDGF-BB stimulation. The crosstalk of crotonylation and ubiquitination in glycolysis is possibly a novel mechanism underlying the VSMC phenotypic remodeling.